THE EVOLUTION OF TAEKWONDO TECHNIQUES AMONG UZBEK ATHLETES: STRENGTH, STRATEGY, AND SUCCESS ON THE GLOBAL STAGE (Zamonaviy ilmiy-texnik tadqiqotlar, 2026)
Uzbekistan's Taekwondo school has gained international recognition for producing elite athletes who excel on the global stage. This article analyzes the technical skills, combat strategies, and physical preparation of Uzbek Taekwondo practitioners. Special emphasis is placed on the refinement of kicking techniques, agility, and defensive strategies. Additionally, the factors contributing to athletes' success in international competitions, such as coaching methodologies and the role of modern technology, are explored. The article discusses the developmental trends of Taekwondo in Uzbekistan and strategies to enhance the global competitiveness of Uzbek athletes.